The consequences of indiscriminate use of Sildenafil Citrate in a young male population aged 18 to 29 years (Research, Society and Development, 2022)
Objective: To describe the consequences of indiscriminate use of Sildenafil Citrate in a young male population aged between 18 and 29 years old. Methods: consists of an integrative literature review, with a qualitative and exploratory approach, carried out in Scielo (Scientific Electronic Library On Line), MEDLINE/Pudmed, Lilacs and Google Scholar databases, referring to the years 2012 to 2022, using the terms: sildenafil citrate, adverse effects, inappropriate use and male population. Articles and other studies that did not fit within the theme, duplicates, in other foreign languages, that did not obey the period between the years 2012 to 2022, paid and that were not even related to the objective of the present research were excluded. Results: studies were presented that showed the characteristics of sildenafil citrate, the mechanisms of action of the concomitant use of the drug and the possible consequences of the excessive use of the drug. Conclusion: The use of phosphodiesterase type 5 inhibitors (IPDE-5) such as Sildenafil Citrate, has been much sought after on a large scale by young men aged between 18 and 29 years, however, unnecessary use by individuals without comorbidities promotes a series of consequences of different levels that can compromise human health, thus strengthening its contraindication for recreational use.